Effects of Omalizumab on Serum Levels of Substance P, Calcitonin Gene-Related Peptide, Neuropeptide Y, and Interleukin-31 in Patients with Chronic Spontaneous Urticaria - Cagdas Boyvadoglu; Hasan Ulusal; Seyithan Taysı; Goknur Ozaydin-Yavuz; Ibrahim Halil Yavuz; Pınar Korkmaz; Huseyin Serhat Inaloz (Mediators of Inflammation)
The mechanism of action of omalizumab in urticaria is still not literally known. This study examines the serum values of substance P (SP), calcitonin gene-related peptide (CGRP), neuropeptide Y (NPY), and interleukin-31 (IL-31) in patients using omalizumab. In this study, 30 patients with chronic spontaneous urticaria (CSU) who were going to be treated with omalizumab and 20 healthy volunteers took part. Demographic data, clinical data, and disease activity scores were noted. For serum SP, CGRP, NPY, and IL-31 values, 10 mL of blood were taken from the patients before starting the treatment, 3 months after the treatment, at the end of the 6th month, and from healthy volunteers all at once. The change in values measured at baseline, 3rd month, and 6th month was analyzed by the Friedman Test. The Mann–Whitney U test was used to compare the parameters obtained from the patients and control groups. The significance level was set at p=0.05. SP, CGRP, NPY, and IL-31 values were all statistically significantly lower in the CSU patient group compared to the control group. After treatment, the levels of SP and CGRP in the serum went up, and the levels of serum IL-31 went down. These changes were statistically significant. This study supports the view that omalizumab does not only affect IgE receptors but also affects mast cells through other mechanisms. According to our knowledge, this is the first study to show that omalizumab therapy and serum CGRP levels are related.